Bridging Terminological Gaps: Challenges in Translating Linguistic Terms Between English and Uzbek - Jurayeva Sarvinoz (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article investigates the challenges and strategies involved in translating linguistic terms from English into Uzbek, with a focus on bridging conceptual and terminological gaps. The study highlights common issues such as lack of equivalent terms, semantic mismatches, and inconsistent usage in bilingual lexicographic resources. Drawing on the theories of Mona Baker, Eugene Nida, and Sandro Nielsen, the article presents a comparative analysis of selected linguistic terms from English and their representations in existing Uzbek dictionaries and glossaries. The research argues for a standardized, corpus-informed approach to bilingual terminology and proposes principles for improving term translation, particularly in academic and educational contexts.